2011
DOI: 10.1128/aem.02780-10
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Somatic Coliphages in Coastal Regions with Different Levels of Anthropogenic Activity in São Paulo State, Brazil

Abstract: Bacteriophages are the most abundant and genetically diverse viruses on Earth, with complex ecology in both quantitative and qualitative terms. Somatic coliphages (SC) have been reported to be good indicators of fecal pollution in seawater. This study focused on determining the concentration of SC and their diversity by electron microscopy of seawater, plankton, and bivalve samples collected at three coastal regions in São Paulo, Brazil. The SC counts varied from <1 to 3.4 ؋ 10 3 PFU/100 ml in seawater (73 sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 39 publications
0
11
0
2
Order By: Relevance
“…The titre of coliphages in all water samples was extremely low (range 0.0125 pfu ml −1 ‐0.28 pfu ml −1 ). This low abundance is lower than previous reports of coliphages in coastal environments that are around 1 × 10 2 pfu ml (Dutka et al, ; Janelidze et al, ; Burbano‐Rosero et al ., ). This may be linked to water quality, since coliphage abundance is known to be linked to faecal contamination.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The titre of coliphages in all water samples was extremely low (range 0.0125 pfu ml −1 ‐0.28 pfu ml −1 ). This low abundance is lower than previous reports of coliphages in coastal environments that are around 1 × 10 2 pfu ml (Dutka et al, ; Janelidze et al, ; Burbano‐Rosero et al ., ). This may be linked to water quality, since coliphage abundance is known to be linked to faecal contamination.…”
Section: Discussionmentioning
confidence: 97%
“…Regarding the diversity of coliphages found in seawater, studies have largely focused on morphological diversity (Muniesa et al, ; Reyes and Jiang, ; Burbano‐Rosero et al ., ; Jofre et al, ) and assessing the number and range of E. coli hosts they can infect. This has shown that many coliphages have a broad host range, with detection of coliphages comprising members of the Siphoviridae and Myoviridae families off the Californian (Reyes and Jiang, ) and Brazilian coasts (Burbano‐Rosero et al ., ) with Siphoviridae being the most frequently observed taxa.…”
Section: Introductionmentioning
confidence: 99%
“…These stations/sites were selected according to their trophic status and level of anthropogenic influence. For instance, Santos is more urbanized and eutrophic than São Sebastião and Ubatuba (Burbano-Rosero et al, 2011). …”
Section: Methodsmentioning
confidence: 99%
“…A substantial amount of data about the presence and levels of indicator phages, mostly coliphages, in all type of surface waters and in very different climatic areas is available (Burbano-Rosero et al, 2011;Contreras-Coll et al, 2002;Ebdon et al, 2007;Haramoto et al, 2005;Ibarluzea et al, 2007;Jiang et al, 2007;Lucena et al, 2003;Rezaeinejad et al, 2014;Taylor et al, 2001). The general trend is that the three groups of phages keep the same proportions as in raw wastewater, but they have reduced the concentration gap with either E. coli or faecal coliform bacteria.…”
Section: Quality Indicators Of Recreational Watersmentioning
confidence: 99%